Effective Sequestration of Acid Orange-7 Dye from Wastewater by using Ricinus Communis Biochar along with Zinc Oxide Nanocomposites - Jameel, Rimsha; Lashari, Saima; Sharif, Muhammad Nabeel; Javaid, Shabnam; Alam, Kashif; Mahmood, Faisal; Ahmad, Waqar; Kokab, Aneeza (Indus Journal of Bioscience Research, 2024)
Water is critical to the survival of life on Earth. Due to increased industrialization, overpopulation, and overexploitation, water quality and assets have deteriorated. To satisfy water demands, it is critical to treat effluents with cost-effective and environmentally friendly adsorbents. In this study, Ricinus communis biochar (RCB) and its nanocomposites with zinc oxide (RCB/ZnO) were employed to remove Acid Orange 7 dye on a batch basis (AO7). The effects of adsorbent dose (1 - 4g/L), dye starting concentration (25 - 500 mg/L), pH (2 - 8), and contact period (15 - 180 min) on the adsorption potential of different adsorbents were investigated and compared. When the IC was varied from 25-200mg/L, the findings showed that the elimination of AO7 by utilizing RCB was 90-70 percent. While the elimination of RCB/ZnONPs were found to be 99-89 percent effective in removing AO7. When compared to earlier investigations, the proposed materials are more efficient and have a higher adsorption capacity. The use of nanoparticle composites for AO7 cleanup at the industrial level has been suggested.